A220 SCREENING AND MANAGEMENT OF LYNCH SYNDROME IN CLINICAL PRACTICE. (15th March 2019) - Jain, A; Singh, H; Shafer, L; Kim, C; Rothenmund, H; Samadder, J; Gupta, S
Abstract: Background: Risk factors for developing colorectal cancer (CRC) at an earlier age include familial risk and hereditary conditions such as Lynch Syndrome (LS). Recently, universal screening for LS has been recommended by several expert groups, suggesting that every new (or age <70) CRC diagnostic sample should undergo mismatch repair immunohistochemistry (MMR-IHC) and/or microsatellite instability (MSI) screening. For patients with LS, surveillance colonoscopy markedly reduces the risk of developing new CRC. The 2015 American College of Gastroenterology (ACG) Guidelines recommend that these individuals should undergo colonoscopy every 1–2 years, beginning at age 20–25. Current Canadian guidelines, however, have not yet recommended: 1) which patients should undergo testing; and 2) the optimal surveillance for patients known to have LS. Aims: (1) To determine the current practice of identifying LS in the US and Canada, and current surveillance and management practices for those diagnosed with LS; (2) To determine variances in current practice and whether they are physician/region dependent or influenced by ease of access to specialist clinics. Methods: An online survey request was sent to practicing gastroenterologists through the Canadian Association of Gastroenterology and ACG. Univariate and multivariate logistic regression analyses were performed to determine the factors associated with testing for LS and separately for follow-up, surveillance and management. Results: A total of 239 participants were recruited, of which 232 were gastroenterologists and included in the analysis. Less than 40% of practicing gastroenterologists indicated that their CRC patients were undergoing screening tests to identify LS. While 42% (N=65) of participants from the US stated that their patients were undergoing universal LS screening, only 9% (N=4) of participants from Canada reported this practice (p<0.001). 83% of respondents had access to a hereditary cancer clinic. There was no statistically significant difference in practice between the physicians that do and do not have access to hereditary clinics (32% testing among those without access to hereditary cancer clinics and 35% among those with access; p=0.450). Appropriate surveillance interval was recommended by most. Conclusions: Overall, LS continues to be an underrecognized condition, resulting in missed opportunities for preventing CRC and other Lynch associated cancers. There is a significant difference in practice between Canada and the US in regard to identification of LS, with suboptimal practice throughout North America. There is ample opportunity for improving recognition of LS through appropriate education and resource management. Funding Agencies: None